AERODYNAMIC EFFECTS OF TRANSITION STRIP APPLICATION ON A MULDICON WING IN LOW-SPEED WIND TUNNEL TESTING (Journal of Transport System Engineering, 2026)
Low-sweep, blunt-leading-edge unmanned combat aerial vehicle (UCAV) configurations exhibit complex vortex separation and inconsistent aerodynamic behaviour at moderate-to-high pitch angles. This study experimentally investigates the effects of leading-edge transition strips on a lambda-planform MULDICON AVT251 wing with a 53° blunt leading-edge sweep. Wind-tunnel tests were conducted in the UTM Low-Speed Wind Tunnel at Reynolds numbers of 3.00×105 to 4.50×105 and pitch angles from −4∘ to 30∘. Lift, drag, pitching-moment coefficients, and surface flow visualisation were analysed for free-transition, 2D-transition, and 3D-transition cases. The results show that transition-strip type strongly affects the onset and progression of leading-edge vortex separation. For the 3D transition case, stall occurred at a=24∘, with CL=1.0183, while Cm remained more predictable up to a=22∘. The findings indicate that the pitching-moment coefficient is highly sensitive to flow topology and vortex-separation behaviour. Overall, the 3D transition strip is recommended to establish a repeatable baseline for future MULDICON flow-field measurements and CFD validation at subsonic.
Keywords: MULDICON wing; Rounded leading-edge; Vortices; Flow separation; Pitching moment coefficient; Wind Tunnel (W/T) Experiments; Transition strips